Proceedings of the Statistical and Social Inquiry Society of Ireland One Hundred and Seventy-Fifth Session: 2021/2022 - SSISI (Statistical and Social Inquiry Society of Ireland, 2022)
Proceedings of the Statistical and Social Inquiry Society of Ireland - One Hundred and Seventy-Fifth Session: 2021/2022
Proceedings of the Statistical and Social Inquiry Society of Ireland - One Hundred and Seventy-Fifth Session: 2021/2022
Keywords: 314.15